A refractory case of subclinical antibody‐mediated rejection due to anti‐HLA‐DQ antibody in a kidney transplant patient. (July 2015) - Fujimoto, Toshinari; Nakada, Yasuyuki; Yamamoto, Izumi; Kobayashi, Akimitsu; Tanno, Yudo; Yamada, Hiroki; Miki, Jun; Ohkido, Ichiro; Tsuboi, Nobuo; Yamamoto, Hiroyasu; Yokoo, Takashi
Abstract: We herein report a refractory case of subclinical antibody‐mediated rejection (AMR) due to anti‐HLA‐DQ antibody in a kidney transplant patient. A 45‐year‐old man was admitted for a protocol biopsy; he had a serum creatinine (S‐Cr) level of 1.8 mg/dL 3 years following primary kidney transplantation. Histological examination revealed moderate to severe inflammatory cell infiltration in the peritubular capillaries. Thorough laboratory examination showed that the patient had donor‐specific antibodies (DSAbs) to DR9 and DQ9. Considering both the histological and laboratory findings, we diagnosed acute antibody‐mediated rejection. The patient underwent 3 days of consecutive steroid pulse therapy, intravenous immunoglobulin (IVIG), and plasma exchange. We also administered rituximab (200 mg/body). Six months after the treatment, a second allograft biopsy revealed the progression of interstitial fibrosis and tubular atrophy and persistence of mild peritubular capillaritis. Further analysis showed that the anti‐DR9 antibodies had disappeared, but that the mean fluorescence intensity value of the anti‐DQ9 antibodies had increased. Therefore, we repeated the plasma exchange and IVIG. Allograft function was stable throughout the course of treatment, and the S‐Cr level remained at 1.8 mg/dL. This case report demonstrates the difficulty of treating AMR due to the presence of anti‐DQ DSAbs and the necessity for subsequent therapies in refractory cases.